THU0565 Immunoglobulin a Nephropathy in Rheumatic Conditions. (9th June 2015) - Rodríguez-Muguruza, S.; Mateo, L.; Sanint, J.; Prior, A.; Garcia, Y.; Riveros-Frutos, A.; Holgado, S.; Martínez-Morillo, M.; Olivé, A.; Tena, X.
Abstract : Background: Immunoglobulin A nephropathy (IgAN) is a form of glomerular disease characterized by microhaematuria. Pathological analysis of renal biopsy is the gold standard for the diagnosis and assessment of disease activity. Association between IgAN and rheumatic conditions has been reported, but the pathophysiological links are unclear. Objectives: To determine the frequency, clinical features, laboratory data, treatment and clinical outcome of IgAN in patients with rheumatic conditions. Methods: Design: retrospective (1984–2014). Hospital: tertiary academic hospital. Referral area: 850, 000 inhabitants. From a total diagnostic population of 2, 754 patients seen by the Rheumatology Department at our centre, we selected patients with a histological diagnosis of IgAN and excluded patients with a diagnosis of gout and osteoporosis. Results: Seven (0.025%) patients had a diagnosis of IgAN, all of them male: by rheumatic condition, 2 (0.009%) of 1, 110 patients with RA, 2 (0.69%) of 287 with ankylosing spondylitis, 1 (0.17%) of 558 with psoriatic arthritis, 1 (0.1%) of 13 with undifferentiated connective tissue disease, and 1 (0.2%) of 450 with diffuse idiopathic skeletal hyperostosis. Median age at diagnosis of IgAN and rheumatic condition was 46.7 and 37 years, respectively (range 37–54/18–67). Mean disease duration was 15.4 years. At presentation, IgAN was suspected by the presence of haematuria (100%), renal failure (100%) or nephritic range proteinuria (28.6%). Mean values of creatinine and 24-hour proteinuria were 1.85 mg/dL and 8.1 g, respectively. Six (85.7%) of the 7 IgAN patients had arterial hypertension. Three (42.85%) patients underwent dialysis after a mean disease duration of 5.6 years (range 2–11), and kidney transplantation was required after 9–25 months. One (14.2%) patient died 7 years after IgAN diagnosis due to pulmonary sepsis at 60 years old. The clinical and analytical parameters are described in Table 1. Conclusions: The frequency of IgAN in our total patient sample was 0.025%. The primary abnormal manifestation IgAN is recurring bouts of haematuria. There was a marked male predominance. The predominant clinical picture was nephrotic syndrome, haematuria and arterial hypertension. References: Jacquet A, Francois H, Frangie C, Yahiaoui Y, Ferlicot S, Micelli C, Mariette X, Durrbach A. IgA nephropathy associated with ankylosing spondylitis is not controlled by infliximab therapy. Nephrol Dial Transplant. 2009 Nov;24(11):3540-2. Azevedo DC, Ferreira GA, Carvalho MA. IgA nephropathy in patients with spondyloarthritis followed-up at the Rheumatology Service of Hospital das Clínicas/UFMG.Rev Bras Reumatol. 2011 Sep-Oct;51(5):417-22. Lee SH, Lee EJ, Chung SW, Song R, Moon JY, Lee SH, Lim SJ, Lee YA, Hong SJ, Yang HI.Renal involvement in ankylosing spondylitis: prevalence, pathology, response to TNF-a blocker.Rheumatol Int. 2013 Jul;33(7):1689-92 Adu D, Berisa F, Howie AJ, Emery P, Bacon PA, McConkey B, McGonigle RJ, Michaels J, Popert AJ.Glomerulonephritis in rheumatoid arthritis.Br J Rheumatol. 1993 Nov;32(11):1008-11. Disclosure of Interest: None declared